2022
DOI: 10.1109/access.2022.3151967
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Transmissions, Propagation and Channel Modelling for IoT Technologies: Applications and Challenges

Abstract: The Internet of Things (IoT) has rapidly expanded for a wide range of applications towards a smart future world by connecting everything. As a result, new challenges emerge in meeting the requirements of IoT applications while retaining optimal performance. These challenges may include power consumption, quality of service, localization, security, and accurate modeling and characterization of wireless channel propagation. Among these challenges, the latter is critical to establishing point-to-point wireless co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 184 publications
(431 reference statements)
0
25
0
Order By: Relevance
“…Multi-UAV cooperation, which is an essential part of this project, could lead to a wide range of uses, including precise geographic localization [9], search and rescue missions [10], intelligent transportation systems [11], target detection [12], disaster tracking and monitoring [13], volcano monitoring [14], delivering medical supplies to otherwise inaccessible regions [15], border patrol missions [16], prevention and control of forest fires [17], UAV control by the brain [18], acting as relays for Internet distribution [19], among others Drones are also extensively employed in the military [20]; for example, the US Navy's LOCUST project hires a swarm of autonomous drones to carry out coordinated military operations [21]. Numerous additional applications are being developed in academia and industry in addition to these marketed ones [22]. Surveying and mapping are two examples of this type of work [23].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-UAV cooperation, which is an essential part of this project, could lead to a wide range of uses, including precise geographic localization [9], search and rescue missions [10], intelligent transportation systems [11], target detection [12], disaster tracking and monitoring [13], volcano monitoring [14], delivering medical supplies to otherwise inaccessible regions [15], border patrol missions [16], prevention and control of forest fires [17], UAV control by the brain [18], acting as relays for Internet distribution [19], among others Drones are also extensively employed in the military [20]; for example, the US Navy's LOCUST project hires a swarm of autonomous drones to carry out coordinated military operations [21]. Numerous additional applications are being developed in academia and industry in addition to these marketed ones [22]. Surveying and mapping are two examples of this type of work [23].…”
Section: Introductionmentioning
confidence: 99%
“…Based on ODAC connectivity dynamics, logical connections are established by sharing beacon messages between sensor nodes. Equation (3) clarifies the basic dynamic acyclic connectivity model [ 39 , 40 ]. According to the model of acyclic graph connectivity principles, the sensor nodes in the WSN are able to configure with associativity rules.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, ref. [ 25 ] developed an empirical channel model for the UAV-to-BS scenario based on path loss and shadowing effects in the LTE network. The results showed that the path loss exponents decrease by increasing the flight height.…”
Section: Related Workmentioning
confidence: 99%